Bacterial subversion of cAMP signalling inhibits cathelicidin expression, which is required for innate resistance to Mycobacterium tuberculosis. Issue 1 (15th March 2017) - Gupta, Shashank; Winglee, Kathryn; Gallo, Richard; Bishai, William R
Abstract: Antimicrobial peptides such as cathelicidins are important components of innate immune defence against inhaled microorganisms, and have shown antimicrobial activity against Mycobacterium tuberculosis in in vitro models. Despite this, little is known about the regulation and expression of cathelicidin during tuberculosis in vivo . We sought to determine whether the cathelicidin‐related antimicrobial peptide gene ( Cramp ), the murine functional homologue of the human cathelicidin gene ( CAMP or LL‐37), is required for regulation of protective immunity during M. tuberculosis infection in vivo . We used Cramp –/– mice in a validated model of pulmonary tuberculosis, and conducted cell‐based assays with macrophages from these mice. We evaluated the in vivo susceptibility of Cramp –/– mice to infection, and also dissected various pro‐inflammatory immune responses against M. tuberculosis . We observed increased susceptibility of Cramp –/– mice to M. tuberculosis as compared with wild‐type mice. Macrophages from Cramp –/– mice were unable to control M. tuberculosis growth in an in vitro infection model, were deficient in intracellular calcium influx, and were defective in stimulating T cells. Additionally, CD4 + and CD8 + T cells from Cramp –/– mice produced less interferon‐β upon stimulation. Furthermore, bacterial‐derived cAMP modulated cathelicidin expression in macrophages. Our results demonstrate that cathelicidin is required for innate resistance to M. tuberculosis in a relevant animal model and is a key mediator in regulation of the levels of pro‐inflammatory cytokines by calcium and cyclic nucleotides. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.